Pengaruh Knowledge Management Terhadap Kinerja Industri Jasa Perbankan (BPD) - Rahmat Dodi Prasetyo; Sawarni Hasibuan (Universitas Mercu Buana, 2019)
The purpose of this study was to determine the effect of the relationship between Knowledge Management on performance in the banking services industry (BPD). This study uses the SEM (Structured Equation Modeling) method using PLS software based on primary data from the questionnaire. Based on the results of the study it can be seen that Knowledge Management has a significant effect on performance. This can be seen based on strong inter-dimensional relationships, where Knowledge Management has a very positive impact on performance. This means that if the implementation of Knowledge Management gets better, it will have a good impact on the company's performance.